Enhanced YOLOv8 Infrared Image Object Detection Method with SPD Module - Ren, Zheng (Journal of Theory and Practice in Engineering and Technology, 2024)
This study proposes an improved deep learning-based method for object detection in low-resolution infrared images in factory environments. Considering the impact of factors such as fog, smoke and insufficient illumination on the detection accuracy, multispectral imaging techniques, especially infrared thermography, are introduced in this study to enhance the recognition capability of the system. We developed a novel algorithm based on YOLOv8 by improving the existing deep learning model and integrated the SPD module, which significantly improves the recognition accuracy of low-resolution images and small objects.The SPD module employs a unique downsampling method on the input feature maps, boosting the model’s ability to detect low-resolution images and small targets while also improving inference speed. Our experimental results on LLVIP and VEDAI datasets demonstrate the superior performance of the proposed method for target detection in infrared images.